PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING (CTL) TYPE INQUIRY TERHADAP HASIL BELAJAR IPS SISWA DI MIN 4 JEMBRANA - Depict Pristine; Ummu Ahyah (HMPS PGMI FTIK IAIN Jember, 2022)
This research was conducted at MIN 4 Jembrana Bali with the object target, namely the lower class or class 3, which aims to (1) get an idea of the application of the CTL Type Inquiry learning model in IPS learning (2) to find an overview of students' IPS learning outcomes taught using the CTL inquiry type learning model (3) knowing the influence on IPS learning outcomes between those taught and the CTL Type Inquiry learning model. This research shows that the CTL Type Inquiry learning model is very influential on students' IPS learning outcomes, the application of the CTL type inquiry learning model in class 3 in this study makes learners or students more active in the learning process. The type of research conducted is experimental research. However, this study shows that the learning model affects the improvement of students' IPS learning outcomes. The influence is due to: First learners of the experimental learning process class are more active and meaningful than the control class. Second, the application of the learning model (CTL) in class three in this study makes learners more active in the learning process. The third one of the principles of CTL learning is constructivists. The essence of the constructivist process is that learners must be able to find and transform a rmasi info into a real situation. the fourth is a discussion activity carried out in the experimental class. Discussion activities in CTL learning build the creation of a Learning Community, so that students who have more abilities will help other learners who are lacking in their compactness. Penelitian ini dilakukan di MIN 4 Jembrana Bali dengan sasaran objek yaitu kelas bawah atau kelas 3, yang dimana bertujuan untuk (1) memperoleh gambaran tentang penerapan model pembelajaran CTL Type Inquiry dalam pembelajaran IPS (2) mendapati gambaran hasil belajar IPS siswa yang diajarkan menggunakan model pembelajaran CTL type Inquiry (3) mengetahui pengaruh tentang hasil belajar IPS antara yang diajarkan dengan model pembelajaran CTL Type Inquiry. Penelitian ini memperlihatkan bahwa model pembelajaran CTL Type Inquiry ini sangat berpengaruh terhadap hasil belajar IPS siswa, penerapan model pembelajaran CTL type inquiry di kelas 3 pada penelitian ini membuat peserta didik atau siswa lebih aktif dalam proses pembelajaran. jenis penelitian yang dilakukan adalah penelitian eksperimen. Namun, dalam penelitian ini menunjukkan bahwa model pembelajaran berpengaruh terhadap peningkatan hasil belajar IPS siswa. Pengaruh tersebut disebabkan oleh: Pertama, peserta didik kelas eksperimen proses pembelajaran lebih aktif dan bermakna daripada kelas kontrol. Kedua, penerapan model pembelajaran (CTL) dikelas tiga pada penelitian ini membuat peserta didik lebih aktif dalam proses pembelajaran. Ketiga salah satu prinsip pembelajaran CTL adalah konstruktivisme. Esensi dari proses konstruktivisme adalah bahwa peserta didik harus dapat menemukan dan mentransformasikan suatu informasi ke situasi nyata. keempat adalah kegiatan diskusi yang dilaksanakan dikelas eksperimen. Kegiatan diskusi dalam pembelajaran CTL membangun terciptanya Learning Community, sehingga siswa yang memiliki kemampuan lebih akan membantu peserta didik lain yang kurang dalam kekompakannya.